Caregiver Management on Dealing with the Effect of Chemotherapy on Pediatric: Literature Review - Trianti, Rana Roidah; Zukhra, Ririn Muthia; Yanhaz, Aidillia; Anggraini, Nurmala (Jurnal Penelitian Perawat Profesional, 2024)
Cancer is the development of abnormal cells that can cause various symptoms during treatment. The most common treatment is chemotherapy. The chemotherapy drugs used affect not only cancer cells but also surrounding normal cells, such as skin, hair follicles and mucosa. Children need to be given measures to reduce the perceived effects of chemotherapy therapy. This study aims to look at the pharmacological and non- pharmacological measures given by caregivers to deal with the effects of chemotherapy. Using literature review using 3 databases namely Google scholar, Pubmed, and ProQuest. The articles used were researched from 2019-2023. Published in Indonesian or English, related to the actions of caregivers to deal with the effects of chemotherapy on children. Based on the analysis of 3 articles, the most common chemotherapy effects were nausea and vomiting, hair loss, and pain. Actions taken in the form of pharmacological actions, namely helping to administer drugs according to what has been prescribed. Non- pharmacological actions include giving eucalyptus oil to nausea and vomiting, inviting children to play therapeutic games to divert pain, using head accessories to deal with hair loss in children.